Implementasi Model Pembelajaran Kooperatif dalam Meningkatkan Kemampuan Membaca dan Menulis Bahasa Arab pada Siswa Sekolah Dasar - Agus Yasin; Muhamad Luthfi Thoyib; Ahmad Farhan Rif’an Najib; Faris Ahsanu Ibadillah (EduInovasi: Journal of Basic Educational Studies, 2024)
Teaching a foreign language at the elementary level comes with its unique challenges. Arabic, with its complex grammar and unique writing system, is often considered a difficult language for beginners to learn. The aim of this research is to investigate the Implementation of Cooperative Learning Models on Improving Arabic Reading Abilities in Elementary School Students and the Impact of Applying the Cooperative Learning Model on Enhancing Arabic Writing Skills in Elementary School Students. In this study, a systematic literature review was conducted by referring to various sources in research databases. An initial search yielded 25 articles published between 2020-2023. Subsequently, the articles were screened, and 7 of them were included in the next phase. The results of this study show that the cooperative learning model also influences students' interest in learning the Arabic language. They feel more comfortable speaking, discussing, and sharing ideas in Arabic, creating a positive learning environment. Students' social skills and collaborative abilities are further developed, which are essential aspects in preparing them for the future.